The effects of virtual racial embodiment in a gaming app on reducing prejudice. Issue 3 (2nd July 2016) - Behm-Morawitz, Elizabeth; Pennell, Hillary; Speno, Ashton Gerding
ABSTRACT: This research experimentally examined the effectiveness of the use of virtual racial embodiment in a digital gaming application for reducing bias against a non-dominant group. The findings of this study advance theory and have practical implications for the design of immersive diversity initiatives. We tested avatar creation and the gaming app as a new modality for stimulating perspective-taking. In addition, we explored how sex and race intersect in virtual embodiment and stereotyping. Results showed that creating and embodying a Black avatar produced more favorable beliefs about African American men, but not African American women, and greater support for "pro-minority" policies in comparison to creating and playing a White avatar. Avatar liking was a significant moderator, but self-presence had no effect.